2010
DOI: 10.1016/s1413-8670(10)70106-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Strongyloides stercoralis hyper-infection in a patient with multiple myeloma

Abstract: Strongyloides stercoralis (S.S.) is a human intestinal parasite, which may lead to complicated strongyloidiasis. We report a case of disseminated strongyloidiasis following the treatment of myeloma. The patient developed skin lesions, respiratory distress, aseptic meningitis and bacterial and fungal sepsis. The diagnosis of strongyloidiasis was established through endotracheal tube secretions. Despite the treatment with Ivermectin and Albendazole, the outcome was fatal. The value of screening for strongyloidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Similar to our case who was associated with Hodgkin lymphoma under treatment, other cases have been diagnosed in association with hematologic malignancy [ [9] , [10] , [11] ]. Adam et al [ 10 ] reported three cases of hyperinfection associated with lymphoma (one of them was classic Hodgkin lymphoma) treated with M.O.P.P.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to our case who was associated with Hodgkin lymphoma under treatment, other cases have been diagnosed in association with hematologic malignancy [ [9] , [10] , [11] ]. Adam et al [ 10 ] reported three cases of hyperinfection associated with lymphoma (one of them was classic Hodgkin lymphoma) treated with M.O.P.P.…”
Section: Discussionsupporting
confidence: 83%
“…But, the strongyloides hyperinfection was not diagnosed until necropsy [ 10 ]. Yacin et al [ 11 ] report a case of disseminated strongyloidiasis following steroids and radiotherapy treatment of myeloma. The patient developed hyperinfection with fatal outcome, even the Ivermectin and Albendazole treatment [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diverse clinical manifestations of strongyloidosis are rarely associated with diagnosis until it is too late to successfully treat the infection, and the pulmonary symptoms are frequently regarded as an exacerbation of COPD [ 19 ]. This leads to the initiation or an increase in steroid therapy, which leads to more rapid progression of the strongloides hyper-infection [ 20 ]. In turn, this results in severe complications that are often fatal [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of strongyloidiasis is based on the observation of juvenile larvae in copro-parasitological studies [ 20 ]. The gold standard for the diagnosis of strongyloidiasis is serial examination of the parasites with routine saline or wet mount preparations, concentration techniques (Baermann concentration, Horadi–Mori filter paper culture, quantitative acetate concentration technique), culturing the samples on agar plates (faecal, sputum, BAL, duodenal aspirate), and histopathological and cytological studies (duodenal biopsy, duodenal aspirate) [ 10, 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have supported an association between S. stercoralis infection hypogammaglobulinaemia associated with multiple myeloma and nephrotic syndrome (Seet et al 2005; Hsieh et al 2006; Yassin et al 2010). …”
Section: Clinical Manifestationsmentioning
confidence: 98%